The Effect of Turmeric Leaf (Curcuma Longa L.) Extract on Leptin, Hmg-Coa Levels, and Blood Vessel Histopathology in Hyperlipidemic Rats Induced by A High-Fat Diet and Propylthiouracil: An in Silico and in Vivo Study - Melissa Angie; Endy Juli Anto; Jekson Martiar Siahaan (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hyperlipidemia is a major cardiovascular risk factor with increasing global prevalence. Turmeric leaves (Curcuma longa L.) contain bioactive compounds with potential antihyperlipidemic properties through modulation of leptin and HMG-CoA reductase. To analyze the effects of ethanolic turmeric leaf extract on leptin, HMG-CoA levels, and blood vessel histopathology in hyperlipidemic rats using in silico and in vivo approaches. Thirty-six male Wistar rats were divided into six groups: normal control (K1), hyperlipidemia control (K2), simvastatin 0.9 mg/kg BW (K3), and turmeric extract at 300 (K4), 600 (K5), and 1200 mg/kg BW (K6). Hyperlipidemia was induced with high-fat diet and propylthiouracil. In silico molecular docking evaluated compound-protein interactions. Phytochemical screening confirmed five bioactive compound classes. In silico analysis showed rutin with strong binding affinities to leptin (−10.2 kcal/mol) and HMG-CoA reductase (−9.8 kcal/mol). The 300 mg/kg dose significantly improved lipid profiles, reduced aortic wall thickness (192.59±6.99 μm), foam cells (24.17±4.31), and HMG-CoA levels (3.45±0.42 ng/mL) (p<0.001). The 600 mg/kg dose optimally restored leptin (485.67±62.34 pg/mL). Ethanolic turmeric leaf extract exerts significant antihyperlipidemic effects by improving lipid profiles, attenuating atherosclerosis, and modulating leptin and HMG-CoA reductase.